On interpolational and extremal properties of periodic perfect splines - Babenko, V. F.; Kovalenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The existence and the extremal property of a periodic perfect spline, which interpolates the given function in mean, are proved.